Risk Management for 4-H Youth Development Work: Large Animals - Horses - Saundra H. TenBroeck; Wendy DeVito; Dale Pracht; Chad Carr; Brittani Kirkland; Georgene Bender (EDIS)
This 13-page publication is one in the series Risk Management for 4-H Youth Development Work. It addresses the risks involving horses at 4-H events. Written by Saundra TenBroeck, Wendy DeVito, Dale Pracht, Chad Carr, Brittani Kirkland, and Georgene Bender and published by the UF/IFAS 4-H Youth Development Department, February 2018. http://edis.ifas.ufl.edu/4h383